The Hubble Tension in Our Own Backyard: DESI and the Nearness of the Coma Cluster - Daniel Scolnic; Adam G. Riess; Yukei S. Murakami; Erik R. Peterson; Dillon Brout; Maria Acevedo; Bastien Carreres; David O. Jones; Khaled Said; Cullan Howlett; Gagandeep S. Anand (The Astrophysical Journal Letters)
The Dark Energy Spectroscopic Instrument (DESI) collaboration measured a tight relation between the Hubble constant ( H _0 ) and the distance to the Coma cluster using the fundamental plane (FP) relation of the deepest, most homogeneous sample of early-type galaxies. To determine H _0 , we measure the distance to Coma by several independent routes, each with its own geometric reference. We measure the most precise distance to Coma from 13 Type Ia supernovae (SNe Ia) in the cluster with a mean standardized brightness of ${m}_{B}^{0}=15.710± 0.040$ mag. Calibrating the absolute magnitude of SNe Ia with the Hubble Space Telescope (HST) distance ladder yields D _Coma = 98.5 ± 2.2 Mpc, consistent with its canonical value of 95–100 Mpc. This distance results in H _0 = 76.5 ± 2.2 km s ^−1 Mpc ^−1 from the DESI FP relation. Inverting the DESI relation by calibrating it instead to the Planck+ΛCDM value of H _0 = 67.4 km s ^−1 Mpc ^−1 implies a much greater distance to Coma, D _Coma = 111.8 ± 1.8 Mpc, 4.6 σ beyond a joint, direct measure. Independent of SNe Ia, the HST Key Project FP relation as calibrated by Cepheids, the tip of the red giant branch from JWST, or HST near-infrared surface brightness fluctuations all yield D _Coma < 100 Mpc, in joint tension themselves with the Planck-calibrated route at >3 σ . From a broad array of distance estimates compiled back to 1990, it is hard to see how Coma could be located as far as the Planck+ΛCDM expectation of >110 Mpc. By extending the Hubble diagram to Coma, a well-studied location in our own backyard whose distance was in good accord well before the Hubble tension, DESI indicates a more pervasive conflict between our knowledge of local distances and cosmological expectations. We expect future programs to refine the distance to Coma and nearer clusters to help illuminate this new local window on the Hubble tension.